Vietnamese EFL Students’ Habits of Using Dictionaries in Translation Practice in ESP Courses - Lien Thi My Tong (Journal of English Language Teaching and Linguistics, 2019)
Doing translation tasks, especially in English-for-Specific-Purposes (ESP) courses, is probably demanding and challenging, which requires students’ utilization of dictionaries and other tools. Thus, this study was conducted to investigate Vietnamese English-as-a-Foreign-Language (EFL) students’ habits of dictionary consultation in ESP translation. The data were collected during a three-week period among 75 third-year EFL students from three classes at University of Languages and International Studies (ULIS), Vietnam National University (VNU) by a combination of quantitative and qualitative methods (i.e. survey questionnaires with a combination of close-ended and open-ended questions). The research highlighted the students’ positive attitudes towards dictionary use together with a high level of its frequency in translating ESP texts, their definite preference for dictionary applications for mobile phones and bilingual dictionaries as well as their prioritized lookups such as equivalents, examples, equivalent usage, and word definitions. In addition, it revealed that the students were confident in their capability of exploiting the dictionaries in ESP translation and thus had little desire for teachers’ assistance and guidance.